The Historical Development and Strategic Change of Wuhan Exhibition Tourism - Zou, Peiyang (Asia Pacific Economic and Management Review, 2025)
As a new form of tourism product that emerged in the 1980s, exhibition and conference tourism has seen rapid development in China since the 1990s. The promotion of exhibition and conference tourism can enhance the reputation and popularity of a region or city, improve urban facilities, and facilitate exchanges and cooperation between regions, significantly boosting economic and social development. In this context, this paper takes Wuhan as a case study to preliminarily explore the basic connotations of exhibition and conference tourism, as well as the advantages and disadvantages, opportunities and challenges of developing such tourism in Wuhan. Based on these findings, some policy recommendations are proposed to support the vigorous development of exhibition and conference tourism in Wuhan.